2015
DOI: 10.1158/2326-6066.cir-15-0086
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Present in Human Ovarian Tumor Microenvironments Induce a Phosphatidylserine-Dependent Arrest in the T-cell Signaling Cascade

Abstract: The identification of immunosuppressive factors within human tumor microenvironments, and the ability to block these factors, would be expected to enhance patients’ anti-tumor immune responses. We previously established that an unidentified factor, or factors, present in ovarian tumor ascites fluids reversibly inhibited the activation of T cells by arresting the T cell signaling cascade. Ultracentrifugation of the tumor ascites fluid has now revealed a pellet that contains small extracellular vesicles (EV) wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 48 publications
6
103
0
Order By: Relevance
“…The absence of a positive spot for GM130 indicated that our exosome preparations were not contaminated with cellular material. As we and others have previously reported, tumor-associated exosomes also express a negatively charged glycerophospholipid, phosphatidylserine (PS) (31), representing a lipid marker expressed on the surface of exosomes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The absence of a positive spot for GM130 indicated that our exosome preparations were not contaminated with cellular material. As we and others have previously reported, tumor-associated exosomes also express a negatively charged glycerophospholipid, phosphatidylserine (PS) (31), representing a lipid marker expressed on the surface of exosomes.…”
Section: Resultsmentioning
confidence: 95%
“…Extracellular vesicles derived from cancer patients’ sera/plasma (32) or from patients’ ovarian tumor ascites fluids (31) have been reported to inhibit the activation of T cells. However, those studies used a method to active the T cells that depended on antibodies to CD3 and CD28 immobilized on antibody-coated beads (32).…”
Section: Resultsmentioning
confidence: 99%
“…However, tumor derived exosomes have been reported to express PS in ovarian cancer [20,38]. Since exosomes fall within the size range of the SUV liposomes used in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in non-apoptotic tumor cells, PS can appear on the outer leaflet, which is accompanied by increased shedding of microvesicles [20,21]. In addition, higher rates of apoptosis within the tumor environment, as well as therapy-induced apoptosis, contribute to bursts of PS exposure and release of PS-expressing apoptotic bodies.…”
Section: Introductionmentioning
confidence: 99%
“…When intratumoral dendritic cells bind and ingest PS-expressing cells, they maintain an immature phenotype that prevents the expression of costimulatory molecules required for functional antigen presentation (26,38). Moreover, PS externalized on tumor-derived microvesicles suppresses activation of T-cell responses (39), and administration of PS-expressing liposomes containing insulin restores tolerance in a murine model of autoimmune diabetes (40). Lastly, although chemotherapy induces tumor cell apoptosis, the concomitant expression of PS on these cells (41,42) further suppresses potential immune-associated antitumor responses (43).…”
Section: Introductionmentioning
confidence: 99%